Redesain Interior Sentra UKM MERR di Surabaya - Luh Ayu Ariesta Damayanti; Mariana Wibowo; Stephanie Melinda Frans (Intra, 2018)
Redesigning Interior of Sentra UKM MERR Surabaya is intended to help the various UKM in the